Kualitas Pelayanan Sebagai Variabel Intervening Antara Kompetensi Pegawai dan Budaya Kerja Terhadap Kepuasan Mitra di Pelayanan Terpadu Satu Pintu Badan Pengusahaan Kawasan Perdagangan Bebas dan Pelabuhan Bebas Batam - Adi Irawan; Gunadi Gunadi; Sri Langgeng Ratnasari; Chablullah Wibisono (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This research aims to investigate the intervening role of service quality on the relationship between employee competence, work culture and customer satisfaction. The objective of research is to understand the effect of employee competence and work culture on customer satisfaction through service quality as intervening at Office of Batam Indonesia Free Zone (BIFZA) Integrated Service (One Stop Office). Research type is quantitative with explanatory method. The research population was all people who have been receiving servives at Office of Batam Indonesia Free Zone (BIFZA) Integrated Service (One Stop Office). This research performed stratified random sampling to get the sample and number of sample was accounted for 175 customers. In order to test hypotheses, this research use path analysis techniques(Path Analysis) as a quantitative analysis, path analysis using a two stage linear regression analyses by using Statistical Package for Social Science (SPSS) version 22.0. The results of analysis found that The results of analysis displayed that 1) employee competence positively and significantly influenced service quality. 2) work culture positively and significantly influenced service quality 3) service quality had no significant influenced customer satisfaction 4) employee competence positively and significantly influenced customer satisfaction 5) work culture positively and significantly influenced customer satisfaction 7) service quality did not play as intervening variable on the relationship between employee competence, work culture and customer satisfaction.